Structure and Function of GPCRs - Lebon, Guillaume; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book introduces readers to the latest advances in G protein-coupled receptor (GPCR) biology. It reviews our current understanding of the structural basis of ligand binding and allosteric mechanisms, following a decade of technological breakthroughs. Several examples of structure-based drug discovery are presented, together with the future challenges involved in designing better drugs that target GPCRs. In turn, the book illustrates the important concept of GPCR biased signaling in physiological contexts, and presents fluorescent- and light-based methodologies frequently used to measure GPCR signaling or to trace their dynamics in cells upon ligand activation. Taken together, the chapters provide an essential overview and toolkit for new scientific investigators who plan to develop GPCR projects. All chapters were written by experts in their respective fields, and share valuable insights and powerful methodologies for the GPCR field.
Structures of Non-rhodopsin GPCRs Elucidated Through X-Ray Crystallography -- NMR Spectroscopy for the Characterization of GPCR Energy Landscapes -- Structure and Activation Mechanism of GPCRs -- Structure-Based Discovery of GPCR Ligands from Crystal Structures and Homology Models -- Integration on Ligand and Structure Based Approaches in GPCRs -- Biased Agonist Pharmacochaperones: Small Molecules in the Toolbox for Selectively Modulating GPCR Activity -- Endosomal PTH Receptor Signaling Through cAMP and Its Consequence for Human Medicine -- Structure and Function Studies of GPCRs by Site-Specific Incorporation of Unnatural Amino Acids -- Fluorescent-Based Strategies to Investigate G Protein-Coupled Receptors: Evolution of the Techniques to a Better Understanding -- Modulation of Metabotropic Glutamate Receptors by Orthosteric, Allosteric, and Light-Operated Ligands. .
Keywords: Medicinal chemistry; Pharmaceutical chemistry; Spectrum analysis; Medicinal Chemistry; Pharmaceutics; Spectroscopy